Analysis of Students' Abilities in Compiling Independent Curriculum Teaching Modules Based on Discovery Learning - Allo, Eda Lolo; Ruslan, Zuhrah Adminira; Cahyani, Vika Puji (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The implementation of the Independent Curriculum requires an increase in the need for prospective teachers who are able to design open modules that are in accordance with student needs. The Discovery Learning model can be applied in the open module of the Independent Curriculum because it can improve problem-solving skills, creativity, and student independence and create an interesting and enjoyable learning experience. This study uses an effective qualitative descriptive method to gain in-depth insight into the development of the Independent Curriculum teaching module based on Discovery Learning by prospective chemistry teacher students. The purposive sampling technique ensures that the research subjects are relevant to the focus of the study, namely students taking microteaching courses with a sample size of 21 students. The identity module component obtained very good criteria, the core activity component obtained sufficient criteria, the learning activity component (discovery learning) obtained very good criteria, and the learning assessment component obtained sufficient criteria. The results of the analysis show that although prospective chemistry teacher students have an understanding of the syntactic psychology of Discovery Learning, its application in the Independent Curriculum requires additional expertise. Students need to plan activities that encourage student stimulation and motivation and practice making more holistic assessments, including diagnostic and summative assessments, to ensure that open modules are prepared in accordance with the Independent Curriculum standards.